Integrating English Games to Enhance Intrinsic Motivation in Young Learners’ Classroom - Asliati Asliati; Rilyani Harahap; Nurliyandi; Cut Mutiara Dewi; Sari Diana (Jumper: Journal of Educational Multidisciplinary Research, 2026)
This study investigated students’ perception of the integrating English games to strengthen intrinsic motivation among young English learners in West Aceh. Using a mixed-methods sequential explanatory design, quantitative data were collected through a questionnaire administered to 27 fifth-grade students at SD Negeri 12 Meulaboh, followed by semi-structured interviews with six participants. The findings indicated that, in term of enjoyment, 100% of students reported that learning English through games was enjoyable and helped them understand the lessons more easily, while 92.5% felt more confident and motivated during the activities. Regarding interest, students showed strong engagement, with all respondents stating that games increased their focus, and over 96% agreeing that games reduced boredom and improved their confidence in responding to teachers’ questions. The results also demonstrate a strong desire to continue learning English using games, as 100% agreed that games increased their liking for English, and more than 96% hoped for similar activities in future lessons. Additionally, students displayed high enthusiasm, with 96.2% feeling closer to their peers and more motivated to continue learning English, while 92.5% stated that games boosted their courage to speak without fear of mistakes.